Exhausting the (Human) Problem - Annalaura Alifuoco (Performance Philosophy)
What happens when exhaustion becomes not defeat but necessity? This article explores exhaustion as both existential condition and methodological proposition—a way to sidestep the human(ist) problem of solutionism. Through the sculptural works of Berlinde De Bruyckere, where organic and synthetic matters merge in states of suspension, we witness exhaustion’s capacity to reshape relations between bodies, forms, and forces.